1985
DOI: 10.1063/1.336314
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Cd(Se,Te) alloy semiconductors: Synthesis, material characterization, and high-efficiency photoelectrochemical cells

Abstract: High-quality Cd(Se,Te) in two compositions were synthesized using the modified Bridgman technique. The Se-rich crystals had the hexagonal structure while the Te-rich phase consisted of crystals with cubic packing. Their quality could be gauged from the high-electron mobility and their low resistivity which suited the purpose of their synthesis, i.e., for high-efficiency photoelectrochemical cells. Photoelectrochemical etching was employed, which resulted in a heavily pitted surface with the density of the etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Results on pulsed laser deposited CdSTe films indicated that the films deposited below x=0.5 in CdS x Te 1-x films exhibited cubic structure, whereas films deposited at values greater than x=0.5 exhibited hexagonal structure [5]. For screen-printed CdS x Te 1-x films, films exhibited cubic structure for x<0.3 and hexagonal structure for higher values of stochiometric coefficient x [8].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Results on pulsed laser deposited CdSTe films indicated that the films deposited below x=0.5 in CdS x Te 1-x films exhibited cubic structure, whereas films deposited at values greater than x=0.5 exhibited hexagonal structure [5]. For screen-printed CdS x Te 1-x films, films exhibited cubic structure for x<0.3 and hexagonal structure for higher values of stochiometric coefficient x [8].…”
Section: Resultsmentioning
confidence: 95%
“…The films prepared in this work possess hexagonal structure for all compositions, whereas earlier reports consist of mixed cubic and hexagonal phases. Clement et al [5] reported results on CdSeTe films with mixed hexagonal and cubic phases. Patil et al [8] also report mixed phases, and the resistivity of the films deposited by the chemical bath deposition in their work possessed high resistivities of the order of 10 4 -10 5 Ω cm, whereas the results of the present work indicate resistivities lower by four orders of magnitude.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The best results were obtained with an aqueous solution of 2.5 M Na2S, 2.5 M S and zero NaOH. The effect of electrolyte composition was studied previously [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…The semiconductors included layered compounds (MX 2 (M = Mo and W, X = S or Se, InSe, ZrSe 2 , In 2/3 PSe 3 , GeSe, etc.) [2][3][4][5][6] and II-VI alloys (such as CdTe, CdSe 1-x Te x with 0<x<1) [7][8][9]. Such study allowed to analyze the effect of the structural dimensionality of the semiconductor on the photoelectrochemical properties and to reach physical parameters of the semiconductor such as type of conductivity, bandgap, direct/indirect optical transition, Fermi level, energy positions of the band edges.…”
Section: Photoelectrochemistry Of Single-crystal Semiconductor Electrmentioning
confidence: 99%